BIOACCUMULATION AND ENZYME ACTIVITY INHIBITION OF PROFENOFOS IN JAPANESE MEDAKA (ORYZIAS LATIPES TEMMINCK AND SCHLEGEL, 1846) - Pascual-Alburo, Rosalyn L. (Journal of Agriculture and Technology Management, 2018)
Please see PDF file.